2008
DOI: 10.1139/x07-152
|View full text |Cite
|
Sign up to set email alerts
|

Growth, resource storage, and adaptation to drought in California and eastern Mediterranean oak seedlings

Abstract: Low recruitment of new plants as currently observed in several California oak species might partly result from insufficient storage of vital resources (reduced ability to regrow after disturbance) or from low adaptation to environmental stress, such as drought. We conducted two studies under divergent environmental conditions to compare seedlings of California oaks with ecologically equivalent species from the eastern Mediterranean region, where recruitment has been substantial over the past 25–30 years. Resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Photosynthesis and stomatal conductance A and gs patterns observed during the spring and summer in this study were consistent with previous studies of the Mediterranean species P. halepensis and Quercus ilex (Baquedano and Castillo 2007;Peñuelas and Llusià 1999;Llusià and Peñuelas 2000), and Q. calliprinos and Q. ithaburensis (Klein et al 2013;Schiller et al 2010;Grünzweig et al 2008). A and gs showed the seasonal trend expected in a Mediterranean climate (Llusià and Peñuelas 2000) except under the near-desertic conditions of Yatir forest (Maseyk et al 2008) where values were extremely low both in spring and summer ( Figs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Photosynthesis and stomatal conductance A and gs patterns observed during the spring and summer in this study were consistent with previous studies of the Mediterranean species P. halepensis and Quercus ilex (Baquedano and Castillo 2007;Peñuelas and Llusià 1999;Llusià and Peñuelas 2000), and Q. calliprinos and Q. ithaburensis (Klein et al 2013;Schiller et al 2010;Grünzweig et al 2008). A and gs showed the seasonal trend expected in a Mediterranean climate (Llusià and Peñuelas 2000) except under the near-desertic conditions of Yatir forest (Maseyk et al 2008) where values were extremely low both in spring and summer ( Figs.…”
Section: Discussionsupporting
confidence: 92%
“…These species are Pinus halepensis L., Quercus calliprinos and Quercus ithaburensis Webb. In this Mediterranean region these species undergo periods of drought and high temperature frequently (Atzmon et al 2004;Grünzweig et al 2008). We measured them in Yatir (in the south, arid) Birya (located north, Mediterranean sub-humid conditions) and Solelim (located north, Mediterranean conditions).…”
Section: Introductionmentioning
confidence: 99%
“…, Grünzweig et al. ). Numerous studies in California foothill oak woodlands have documented increased rates of oak seedling establishment in wetter years (Griffin , Borchert et al.…”
Section: Methodsmentioning
confidence: 99%
“…Leaf surface reduction is a further protective mechanism of dehydration avoidance restraining water loss while maximizing carbon gain, and keeping minimum « md above the threshold of xylem embolism under increasing drought intensity. Lower SLA has long been shown to be an adaptive response to drought (Abrams, 1994;Cunningham et al, 1999;Grünzweig et al, 2008) or an indicator of resource conditions (Cornelissen et al, 2003). Ramírez-Valiente et al (2011) found that cork oak's SLA was negatively correlated with annual shoot growth and positively related to annual growth.…”
Section: Cork Oak Drought Avoidance Strategies and Resiliencementioning
confidence: 99%